Prediction & Classification of Crimes Against Women - Agarwal, Ankit; Malathy, C.; Mukherjee, Nilesh (International Journal of Psychosocial Rehabilitation, 2020)
Crime is one of the significant social-issue in a nation influencing open well-being and the most ideal approach to end violations is to keep it from occurring in any case by tending to its root and auxiliary causes. In this paper it is proposed to focus on the 11 different types and sub-types of crimes (rape, dowry deaths, cruelty by husband or his relatives, indecent representations of women, immoral trafficking, etc) related to women and is a major concern for their safety. Our work involves various tasks to be achieved which can be classified as : cleaning the data set, analysis and visualization of the data for better understanding , predicting the crime rate for the upcoming year using supervised machine learning algorithm and finally make a classification of top 3 crimes(with the help of plotly dash to make a simple yet effective web-interface for the user).